Changes in the Distribution of the α3 Na+/K+ ATPase Subunit in Heterozygous Lurcher Purkinje Cells as a Genetic Model of Chronic Depolarization during Development. (27th February 2014) - McFarland, Rebecca; Zanjani, Hadi S.; Mariani, Jean; Vogel, Michael W.
Abstract : A common assumption of excitotoxic mechanisms in the nervous system is that the ionic imbalance resulting from overstimulation of glutamate receptors and increased Na + and Ca ++ influx overwhelms cellular energy metabolic systems leading to cell death. The goal of this study was to examine how a chronic Na + channel leak current in developing Purkinje cells in the heterozygous Lurcher mutant (+/ Lc ) affects the expression and distribution of the α 3 subunit of the Na + /K + ATPase pump, a key component of the homeostasis system that maintains ionic equilibrium in neurons. The expression pattern of the catalytic α 3 Na + /K + ATPase subunit was analyzed by immunohistochemistry, histochemistry, and Western Blots in wild type (WT) and +/ Lc cerebella at postnatal days P10, P15, and P25 to determine if there are changes in the distribution of active Na + /K + ATPase subunits in degenerating Purkinje cells. The results suggest that the expression of the catalytic α 3 subunit is altered in chronically depolarized +/ Lc Purkinje cells, although the density of active Na + /K + ATPase pumps is not significantly altered compared with WT in the cerebellar cortex at P15, and then declines from P15 to P25 in the +/ Lc cerebellum as the +/ Lc Purkinje cells degenerate.